Cumulative Dividend Preferred Shares between Prohibition and Permissibility: A Comparative Analytical Study - Mohammed, Mohammed; Gatea, Haider (Journal of Legal Sciences, 2026)
Within the framework of capital markets and the regulation of commercial companies, the cumulative preferred share emerges as a legal instrument of a composite nature, occupying an intermediate position between the ordinary share and a debt instrument. It does not lose its character as a share, nor does its holder become a creditor of the company. Rather, the holder remains a shareholder in the company’s capital, while enjoying a preferential financial privilege that distinguishes them from ordinary shareholders, namely the priority to receive the prescribed dividends whenever the conditions for their distribution are met. The distinctiveness of this share lies in the fact that the non-distribution of dividends in a given financial year does not extinguish the holder’s right to the preferred dividends. Instead, such dividends are carried forward to subsequent years, accumulating in the holder’s favor, to be satisfied once distributable profits are available in the future and before ordinary shareholders participate in the distribution of dividends. Accordingly, the right arising from this share is not a debt immediately due from the company merely because no distribution has been made, nor does it impose an immediate payment obligation outside the rules governing capital and dividend distribution. Rather, it constitutes a deferred financial right, conditional upon the existence of distributable profits and the adoption of a lawful resolution to distribute them in accordance with the law and the company’s articles of association. Comparative law has recognized this type of share in different forms. In American law, particularly in the state of Delaware, the regulation of preferred shares rests on a clear contractual foundation. Their rights and privileges are derived from the certificate of incorporation or the company’s constitutive instrument, and such privileges are not presumed merely from the preferred character of the share; they must be expressly provided for. thus, the cumulative nature of dividends is not an automatic consequence of a preferred share, but arises only where it is stipulated in the instrument of issuance or in the document establishing the rights attached to the share. in French law, by contrast, the legislature has adopted a more explicit regulatory approach through the system of preference shares (actions de preference), which permits the granting of certain shareholders distinct financial or administrative rights, within limits set by law and without undermining the essential structure of the company, the protection of capital, or the principle of relative equality among shareholders. Preference is therefore no longer merely a contractual innovation; it has become a legally regulated instrument that may assume various forms, including preference in dividends, preference upon liquidation, or preference in certain rights attached to the share. In Iraqi law, however, the issue appears more cautious and restrictive. Iraqi legislation, in its general form, does not contain an express and comprehensive regulation of cumulative preferred shares in the manner known in certain comparative legal systems. Moreover, its traditional rules are founded upon important considerations, including the uniform nominal value of shares, the relative similarity of shareholders’ legal positions, the connection between voting rights and the share, and the separation between the share as a unit of capital and the bond as an instrument of indebtedness. These rules make it difficult to import the foreign model of cumulative preferred shares fully and directly into the Iraqi legal system. nevertheless, such caution does not preclude the possibility of conceiving a limited Iraqi gateway for this instrument, provided that the preference remains confined to its purely financial scope, namely priority in the accumulation of dividends upon the existence of distributable profits, without transforming into a fixed and absolute obligation of the company, without granting the holder the status of a creditor, and without violating mandatory rules relating to capital or impairing the essence of shareholding. What is acceptable in this respect is not the creation of a concealed debt in the form of a share, but rather the establishment of a conditional and deferred dividend preference that remains tied to the nature of the share and to the rules governing the distribution of profits. Accordingly, the cumulative preferred share may be legally understood as a share that grants its holder financial priority in dividends, not a creditor’s claim against the company. its legal delicacy lies in preserving the balance between two considerations: recognizing the needs of modern finance and the flexibility required in capital instruments, while preventing any circumvention of the mandatory rules that distinguish capital from debt and safeguard shareholders, creditors, and the integrity of the company’s legal order.